Analysis and countermeasure to improve production system performance by using overall equipment effectiveness at bi technologies sdn. Bhd. - Beh, Alicia (2013)
To compete in global market, no organization will tolerate losses. Overall Equipment Effectiveness (OEE) is a novel technique to measure the effectiveness of a machine and it truly reduces complex production problems into simple and intuitive presentation of information. It considers all important measures of productivity. An attempt has been done to measure and analyze existing Overall Equipment Effectiveness (OEE) at BI Technologies Sdn. Bhd. in hope to reduce unplanned downtime losses on equipment failure and tooling damage to maximize the productivity. Before obtaining the data to calculate the existing OEE value, the product or process that have the most defects need to be identified which is component HM72A-10 series at Moulded Inductor area. The methods used to analyze these various causes were Ishikawa diagram, 5 Whys and 5W1H. After knowing the causes of various activities that leads to high rates of defects, then recommendations for improvements that could be used by BI Technologies were ready to be made